2010
DOI: 10.1103/physrevlett.104.096804
|View full text |Cite
|
Sign up to set email alerts
|

Missing Atom as a Source of Carbon Magnetism

Abstract: Atomic vacancies have a strong impact in the mechanical, electronic, and magnetic properties of graphenelike materials. By artificially generating isolated vacancies on a graphite surface and measuring their local density of states on the atomic scale, we have shown how single vacancies modify the electronic properties of this graphenelike system. Our scanning tunneling microscopy experiments, complemented by tight-binding calculations, reveal the presence of a sharp electronic resonance at the Fermi energy ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
778
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 840 publications
(843 citation statements)
references
References 37 publications
60
778
3
2
Order By: Relevance
“…5,17,73,101,105,106 Point defects give rise to localized states near the Fermi energy in sp 2 -bonded materials, leading to the protrusions that appear in STM images. 17 Some vacancy-type 107 and SW 98 defects open a local bandgap (up to 0.3 eV) in graphene, which may be quite important for defect-mediated engineering of the local electronic structure. Some of these defects have already been generated by electron irradiation (J. Kotakoski et al, submitted for publication).…”
Section: Properties Of Defective Graphenementioning
confidence: 99%
“…5,17,73,101,105,106 Point defects give rise to localized states near the Fermi energy in sp 2 -bonded materials, leading to the protrusions that appear in STM images. 17 Some vacancy-type 107 and SW 98 defects open a local bandgap (up to 0.3 eV) in graphene, which may be quite important for defect-mediated engineering of the local electronic structure. Some of these defects have already been generated by electron irradiation (J. Kotakoski et al, submitted for publication).…”
Section: Properties Of Defective Graphenementioning
confidence: 99%
“…Recent studies have shown that these defects can indeed give rise to localized resonant states that are pinned in energy close to the Dirac point 32,[54][55][56] . When a negative back gate is applied these localized states reside well above the Fermi energy and therefore cannot trap the hot carriers that have characteristic energies only slightly above .…”
Section: S15 Scanning Gate Thermometry Of Hbn/graphene/hbn Devicementioning
confidence: 99%
“…The presence of defects modifies electronic, magnetic and mechanical properties of materials. For example vacancies generated by ion irradiation of graphene give rise to magnetic moments [11,12] and the most probable form of defects produced by irradiation are single vacancies [13]. Moreover coherence exchange of spin between such magnetic moments and the spectrum of fermions of the host graphene leads to unconventional Kondo effect in graphene [14,15].…”
Section: Introductionmentioning
confidence: 99%